Find answers to your questions and expand your knowledge with IDNLearn.com. Our experts provide timely and precise responses to help you understand and solve any issue you face.
Sagot :
To solve the equation [tex]\( -2 \sqrt{x} + 4 = -12 \)[/tex], follow these steps:
1. Start by isolating the term with the square root on one side. Subtract 4 from both sides of the equation:
[tex]\[ -2 \sqrt{x} + 4 - 4 = -12 - 4 \][/tex]
Simplifying this, we get:
[tex]\[ -2 \sqrt{x} = -16 \][/tex]
2. Next, divide both sides of the equation by -2 to isolate the square root term:
[tex]\[ \frac{-2 \sqrt{x}}{-2} = \frac{-16}{-2} \][/tex]
Simplifying this, we get:
[tex]\[ \sqrt{x} = 8 \][/tex]
3. Now, square both sides to eliminate the square root:
[tex]\[ (\sqrt{x})^2 = 8^2 \][/tex]
Simplifying this, we get:
[tex]\[ x = 64 \][/tex]
Therefore, the solution to the equation [tex]\( -2 \sqrt{x} + 4 = -12 \)[/tex] is [tex]\( x = 64 \)[/tex].
The correct answer is:
D. 64
1. Start by isolating the term with the square root on one side. Subtract 4 from both sides of the equation:
[tex]\[ -2 \sqrt{x} + 4 - 4 = -12 - 4 \][/tex]
Simplifying this, we get:
[tex]\[ -2 \sqrt{x} = -16 \][/tex]
2. Next, divide both sides of the equation by -2 to isolate the square root term:
[tex]\[ \frac{-2 \sqrt{x}}{-2} = \frac{-16}{-2} \][/tex]
Simplifying this, we get:
[tex]\[ \sqrt{x} = 8 \][/tex]
3. Now, square both sides to eliminate the square root:
[tex]\[ (\sqrt{x})^2 = 8^2 \][/tex]
Simplifying this, we get:
[tex]\[ x = 64 \][/tex]
Therefore, the solution to the equation [tex]\( -2 \sqrt{x} + 4 = -12 \)[/tex] is [tex]\( x = 64 \)[/tex].
The correct answer is:
D. 64
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.